Spatial productivity and efficiency spillovers in the presence of transient and persistent efficiency: evidence from China's provinces - Hazwan Haini (Cogent Economics & Finance, 2020)
This study examines the spatial productivity and efficiency spillovers of Chinese provinces using a spatial Durbin production frontier model that accounts for persistent and transient efficiency using a panel dataset of Chinese provinces from 1985 to 2017. The role of spatial effects is often overlooked in the literature, yet technological progress can spillover and diffuse from provinces and promote regional growth. The spatial Durbin production frontier model allows for the decomposition of direct and indirect (spillover) total factor productivity (TFP) growth, as well as the gross direct and indirect efficiency of the respective provinces. The estimated results show that spatial productivity and efficiency spillovers are positive and lead to higher productivity growth. On average, indirect effects provide an additional TFP growth of 3.1% and an additional efficiency spillover of 18.98%. However, the estimated results also show that TFP growth is declining over time and there is room for efficiency gains if persistent efficiency is increased. These should be addressed through further reforms and policies that promote sustainable growth.
Keywords: C23; O49; R11; O47; 330; China; productivity; efficiency; spatial regression; spillovers; TFP